On the corrosion of ductile cast iron by sulphate reducing bacteria—implications for long-term nuclear waste repositories - Tamisier, Marc; Musat, Florin; Richnow, Hans-Hermann; Vogt, Carsten; Schmidt, Matthias (Frontiers in Geochemistry, 2023)
Ductile cast iron is a candidate material for long term nuclear waste repository canisters. However, little is known about microbial corrosion of this material, a phenomenon threatening the integrity of the repository. Here, the corrosion of ductile cast iron (92.73% to 94.19% Fe) and mild steel (~99.37% Fe) by the sulphate reducing bacterium Desulfopila corrodens were compared. Particular attention was payed to the impact of graphite nodules in ductile cast iron on the corrosion. The two materials developed similar crusts after 36 days. However, in the early corrosion stages different mineral compositions of the formed crusts were observed, e.g. dome shaped minerals (< 1µm) that formed on mild steel were absent on ductile cast iron. Further, iron sulphide was formed equally on all surfaces, the iron and graphite nodules.Our results contribute to the understanding of how microbial activity drives the corrosion of ductile cast iron made structures (e.g. canisters) in long-term nuclear waste repositories, particularly with respect to the mineral composition of the crust at different stages of the corrosion process. We propose that under the conditions used in this study, the ductile cast iron and mild steel bio-corrode similarly on long time scales which makes both material not favourable for use in long term nuclear waste repository with regard to microbial corrosion.